Immigration - a way out of the Swedish rural population crisis? - Mats Johansson (European Regional Science Association (ERSA), 2016)
During the past decades immigration to Sweden has increased sharply and this has had an impact on urban as well as rural population development. During the era of labour immigration the immigrants were spread all over the country in line with labour demand but during the past decades the with accentuated refugee immigration the immigrants have instead been concentrated to the large cities and especially then to the metropolitan areas. But there are also opposite forces that have stimulating effects on the rural population development as the immigrants have increased both in relative and absolute terms. Even if the internal migratory movements still are of rural-urban character the huge immigration flows seem to have hampering effects on the rural depopulation tendencies at least in the short term as many of the refugees centres are localized in rural areas and some of the immigrants stay in their new surroundings. The result has been that the negative migration surplus has been substituted by a positive one even for many rural areas in Sweden and the population decrease in the rural areas has been - at least officially - hampered. The results must, however, be interpreted with some scepticism as it must be borne in mind that the refugees formally are immigrants in the municipalities where they got their residence permit. After that, they are internal migrants in the second round if they move to other places in Sweden - that often is the case - as they are then registered as foreign-born internal migrants but not immigrants. This might mean that the immigrants hamper the net out-migration intensities in the first round but stimulate them in the second. Anyhow, without immigrants the problematic demographic situation in many rural areas in Sweden would be worsening as some of the immigrants stay in their 'new' settlement communities even if these are out-migration areas. In many cases the negative net-migration intensities are changed to positive net-migration intensities as a consequence of immigration. Another aspect is the potential hampering effects on the ageing process as many of the immigrants are relatively young and with a higher fertility but here the effects on natural population increase are hampered by the skewed gender structure. These divergent demographic processes are analysed based on the development paths between 1970 and 2014 in differing Swedish urban-rural regions - a period with drastic changes in the geographical migration patterns but also in the Swedish immigration policy.
Keywords: J; 330; Migration; ageing; urban-rural relations